Students' perceptions of interactive multimedia mediated web-based learning: A Malaysian perspective - Neo, Mai; Neo, Tse Kian; Yap, Wei Li (2008)
While using the Web can be viewed nowadays as a new platform for delivery of course materials, there are still many educators who look to the Web as a replacement for their current teaching methods. This paper sought to investigate students' perceptions towards an interactive web-based learning environment, which consisted of using multimedia-mediated web-based learning modules, created based on Mayer's (2001) design guidelines, and the use of weblogs to capture the student learning process. Students were given pre-and posttests, and a survey to ascertain their reactions and attitudes toward this mode of learning. The results obtained were very positive and encouraging. Students generally found the multimedia-mediated web-based learning environment to be enjoyable and motivating, and were able to demonstrate their learning and skills of the subject domain via their weblogs. Results also gave strong support for the use of multimedia in learning modules that followed proper design guidelines which would better engage students in their learning.